Synthesizing Hadith Criticism and Linguistics: An SFL-Based Validation of Al-Wahidi’s Asbab al-nuzul Narrations - Irma Riyani; Ai Yeni Yuliyanti; Mu'min Mu'min (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
This study proposes a novel interdisciplinary framework for validating the Asbab al-nuzul database in Al-Wahidi’s seminal work by utilizing Systemic Functional Linguistics (SFL). While the significance of Asbab al-nuzul (occasions of revelation) is paramount for Qur’anic contextualization, traditional hadith transmissions often encounter issues of linguistic ambiguity and structural inconsistency. This research moves beyond a purely quantitative assessment to emphasize the theoretical utility of SFL as a rigorous validation tool. By systematically segmenting transmission events specifically those utilizing formal phrases such as Akhbarana and Haddatsana into discrete categories of speaker, recipient, and content, this approach effectively resolves ambiguities within the chain of narration. Using Surah Al-Baqarah as a case study, the analysis demonstrates how identifying these thematic and interpersonal elements allows for a more reliable verification of hadith integrity. The findings conclude that SFL analysis provides a robust, qualitative framework for clarifying the reliability of asbab al-nuzul transmissions, thereby supporting more accurate thematic exegesis (Mawdlu'i). This study offers a scalable methodology for modern Islamic scholarship, enabling a deeper, linguistically grounded validation of classical religious texts